Elementos da constituição da identidade docente de professoras iniciantes da educação infantil e do ensino fundamental - anos iniciais - Pinheiro, Tarciana dos Santos (Universidade Federal de São Carlos, 2020)
Teacher education and professional development are occupying considerable prominence in the Brazilian educational research scenario. We understand that there are several aspects that enable this development, and that the professional identity of novice teachers who work in early childhood education and in the early years of elementary school is permeated by constant challenges. Thus, the research question is: In what ways does the constitution of novice teachers’ professional identity, working in early childhood education and in the early years of elementary school, occur? We seek to identify and characterize the elements of personal and professional trajectories that constitute the novice teachers’ professional identity of early childhood education and the early years of elementary school. The research takes place in an induction program - Hybrid Mentoring Program – HMP (UFSCar) - developed by the research group named Teacher Education and other educational agents that aims to provide a mentoring process in which mentors (experienced teachers) accompany beginners aiming to minimize / overcome the difficulties faced at the novice teachers’ career. In methodological terms we propose a qualitative descriptive-analytical study. Regarding the process of data production and analysis, the research is supported by the use of narratives elaborated in the virtual learning environment and oral narrative interview. The data were analyzed from an understanding-interpretative perspective that made it possible to perceive the elements of the set of novice teachers’ life-education stories. The results showed that during the personal and professional trajectories there are some tensions that permeate the beginning of teaching. We visualize a conflicting professional life period, because, besides marking the passage from student to teacher, there are personal aspects such as beliefs and values that influence the construction of conceptions of teaching practice. The research proved the importance of a continuous education, demonstrating the essential relevance of induction programs, once we realize the indispensable factor in the teacher's identity constitution - the accompaniment of these professionals at the moment they enter schools facilitates the tensions, opening new perspectives to broaden the theoretical / methodological repertoires of teachers, as well as provide paradigms changes. Thus, the various aspects of the process professional identity constitution were confirmed, proving to us the importance of analyzing teachers' personal and professional trajectories. After all, understanding these elements is, in fact, necessary to seek new ways of intervening in the continuous formation of these professionals.
Elements of the constitution of the teaching identity of beginning teachers in childhood education and fundamental education - initial years
Keywords: Identidade docente; Narrativas de formação; Início da docência; Educação infantil; Ensino fundamental – anos iniciais; Indução à docência; Teacher ́s identity; Narratives; Beginning of teaching; Child education; Elementary school - early years; Induction to teaching; CIENCIAS HUMANAS::EDUCACAO